A physically short fatigue crack growth approach based on low cycle fatigue properties. (October 2017) - Wu, S.C.; Xu, Z.W.; Yu, C.; Kafka, O.L.; Liu, W.K.
Highlights: A low cycle fatigue based FCG model has been proposed for both long and physically short crack. A proper crack opening function is used for physically short cracks. Provides an appealing alternate to standard NASGRO. Abstract: This work proposes an improved and simplified fatigue life equation called LAPS, formulated from low cycle fatigue data of smooth specimens and the Rice-Kujawski-Ellyin asymptotic field, with proper crack opening functions for closure effects. The model captures both long and physically short fatigue crack growth behavior, but the emphasis of this contribution is on the modifications for physically short cracks based on empirical models found in the literature. The predictions for physically short cracks from this model coincide well with experimental data for the railway axle used steel 25CrMo4. The predictions for long cracks match well with data from a variety of different metals. This makes the model a suitable alternative, e.g. to NASGRO, for engineering applications.